2017
DOI: 10.1111/jop.12585
|View full text |Cite
|
Sign up to set email alerts
|

Role of sialyl 6‐sulfo Lewis X in antitumor immunity against oral squamous cell carcinoma

Abstract: Sialyl 6-sulfo LeX is displayed not only on HEV-like vessels but also on OSCC cells and may potentially function in antitumor immunity against OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We previously demonstrated induction of HEV-like vessels in chronic inflammatory conditions, including chronic Helicobacter pylori gastritis, 15 17 ulcerative colitis, 18,19 autoimmune pancreatitis, 20 chronic prostatitis associated with benign prostatic hyperplasia, 21 and eosinophilic chronic rhinosinusitis, 22 as well as in malignant tumors including bladder urothelial carcinoma 23 and oral squamous cell carcinoma. 24 In these studies, we detected PNAd on HEV-like vessels using the monoclonal antibody MECA-79, whose epitope is known to be 6-sulfo N -acetyllactosamine attached to extended core 1 O -glycans, 25,26 which overlaps with sialyl 6-sulfo Lewis X, the L-selectin recognition determinant. Here, we performed quantitative immunohistochemical analysis of a total of 36 LP cases (19 OLP and 17 CLP) to assess induction of PNAd-expressing HEV-like vessels.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated induction of HEV-like vessels in chronic inflammatory conditions, including chronic Helicobacter pylori gastritis, 15 17 ulcerative colitis, 18,19 autoimmune pancreatitis, 20 chronic prostatitis associated with benign prostatic hyperplasia, 21 and eosinophilic chronic rhinosinusitis, 22 as well as in malignant tumors including bladder urothelial carcinoma 23 and oral squamous cell carcinoma. 24 In these studies, we detected PNAd on HEV-like vessels using the monoclonal antibody MECA-79, whose epitope is known to be 6-sulfo N -acetyllactosamine attached to extended core 1 O -glycans, 25,26 which overlaps with sialyl 6-sulfo Lewis X, the L-selectin recognition determinant. Here, we performed quantitative immunohistochemical analysis of a total of 36 LP cases (19 OLP and 17 CLP) to assess induction of PNAd-expressing HEV-like vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of HEVs has been reported in oral lesions with malignant potential ( 53 , 54 ), but HEV development at different stages of oral cancer development and progression is not well described. In OSCC, HEVs are more frequently found in early-stage tumors (T1-T2) than advanced tumors (T3-T4) ( 21 , 55 ). Here we showed that the number of HEVs increased significantly during progression of tongue lesions, suggesting that early changes in the tongue mucosa initiates HEV formation that is maintained during tumor initiation and progression.…”
Section: Discussionmentioning
confidence: 99%